Aesthetics of religious coexistence and tolerance in the Shafak’s Turkish novel - Adel, Mohammed Abou (Penerbit Universiti Kebangsaan Malaysia, 2023)
This paper explores the novel “Forty Rules of Love” by Elif Shafak, which evokes the historical personality of the great scholar Jalal al-Din al-Rumi, dubbed by the West “the Shakespeare of the Islamic world”. He was known for his moderation and tolerance, for his call to coexistence and fraternity between the members of different religions, and his condemnation of violence and extremism of all kinds. So, the novel strives to change the misconceptions of the West regarding the Asian countries of the East and to challenge the negative attitude towards Islam, known nowadays as Islamophobia. The paper aims to address the evil of fanaticism and violence and introduce the Western reader to the sublime spiritual aesthetics of the East, which starkly contrast to the savage image of Islam as presented by the media. By studying the novel, which has been translated into more than fifty languages, the paper also seeks to emphasise the role of literature, in general, in spreading cultural awareness among fellow human beings so that people can live in peace and safety.